Electrochemical study of graphene-ionic liquid composites - Noor Hidayah , Sukardi (2011)
This project entitled electrochemical study of graphene-ionic liquid composites. A unique combination of excellent electrical, thermal and mechanical properties has made graphene a multi-functional reinforcement for polymers. The objectives of this project are: to fabricate graphene by electrolytic exfoliation and to characterize graphene-ionic liquid composites by physical, chemical characterization and electrochemical study. In this project, graphene will be fabricated by using electrolytic exfoliation method. Then, FTIR spectroscopy and BET analyzer were used to characterize exfoliated graphene. In order to measure electrochemical behaviour of graphene-ionic liquid composite, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used. Results show that graphene-ionic liquid composites exhibit linear redox diffusion on the surface, a good criteria for electrode material. This can be observed via cylic voltammetry. Graphene-ionic liquid composites also show good conductivity with low impedance value in the Nyquist plot. This material can be a new versatile soft material with numerous advantages.